Building Entrepreneurial Intention: The Role of Education, Environment, and Self-Efficacy in Driving MSME Success - Fahri Haikal; R Hario Sulistianto; Bella Suryani (Jurnal Manajemen dan Kewirausahaan, 2025)
Entrepreneurship has become a crucial solution for addressing unemployment and economic inequality in Indonesia, where micro, small, and medium-sized enterprises (MSMEs) form the backbone of the national economy. Recent trends, however, reveal a decrease in entrepreneurial motivation among university students, raising worries regarding the viability of MSMEs. This study examines the influence of entrepreneurship education and familial environment on students' entrepreneurial aspirations, with self-efficacy serving as a mediating variable. This study's originality lies in emphasizing the mediating function of self-efficacy within the Indonesian environment, where students encounter both opportunities and obstacles in engaging in entrepreneurial endeavors. This study utilized a quantitative survey methodology with a cross-sectional design, encompassing 221 students from several institutions in Jakarta who had engaged in entrepreneurship-related courses. Data were gathered with a standardized questionnaire and analyzed via Structural Equation Modeling. The findings demonstrate that entrepreneurship education and the familial environment substantially affect students' entrepreneurial intentions, both directly and indirectly via self-efficacy. Entrepreneurship education significantly influences self-efficacy, which in turn amplifies entrepreneurial intention. The familial environment significantly contributes to the development of pupils' confidence and drive to participate in entrepreneurial endeavors. These findings imply that fostering entrepreneurial interest among students requires not only effective curriculum design but also active family support to strengthen self-efficacy. The study recommends that universities, families, and policymakers collaborate in creating a conducive ecosystem that encourages students to pursue entrepreneurship, thereby contributing to the growth and sustainability of MSMEs in Indonesia.